The Differences between the Effects of a Nanoformulation and a Conventional Form of Atrazine to Lettuce: Physiological Responses, Defense Mechanisms, and Nutrient Displacement - Wu, Juan; Zhai, Yujia; Monikh, Fazel Abdolahpur; Arenas-Lago, Daniel; Grillo, Renato [UNESP]; Vijver, Martina G.; Peijnenburg, Willie J. G. M. (American Chemical Society (ACS), 2021)
The rapid development of nanotechnology influences the developments within the agro-sector. An example is provided by the production of nanoenabled pesticides with the intention to optimize the efficiency of the pesticides. At the same time, it is important to collect information on the unintended and unwanted adverse effects of emerging nanopesticides on nontarget plants. Currently, this information is limited. In the present study, we compared the effects of a nanoformulation of atrazine (NPATZ) and the nonencapsulated atrazine formulation (ATZ) on physiological responses, defense mechanisms, and nutrient displacement in lettuce over time with the applied concentrations ranging from 0.3 to 3 mg atrazine per kg soil. Our results revealed that both NPATZ and ATZ induced significant decreases in plant biomass, chlorophyll content, and protein content. Additionally, exposure to NPATZ and ATZ caused oxidative stress to the lettuce plant and significantly elevated the activities of the tested ROS scavenger enzymes in plant tissues. These results indicate that NPATZ and ATZ cause distinct adverse impacts on lettuce plants. When comparing the adverse effects in plants after exposure to NPATZ and ATZ, no obvious differences in plant biomass and chlorophyll content were observed between NPATZ and ATZ treatments at the same exposure concentration regardless of exposure duration. An enhanced efficiency of the active ingredient of the nanopesticide as compared to the conventional formulation was observed after long-term exposure to the high concentration of NPATZ, as it induced higher impacts on plants in terms of the end points of the contents of protein, superoxide anion (O2˙-), and MDA, and the activities of stress-related enzymes as compared to the same concentration of ATZ. Furthermore, exposure to both NPATZ and ATZ disrupted the uptake of mineral nutrients in plants, and the differences in the displacement of nutrients between the NPATZ and ATZ treatments depended on the element type, plant organ, exposure concentration, and time. Overall, the application dose of a nanopesticide should balance their increased herbicidal efficiency with the long-term adverse effects in order to maximize the desired impact while minimizing adverse impacts; only then will we be able to understand the potential impact of nanopesticides on the environment.
Keywords: herbicide; nanopesticide; nontarget plant; oxidative stress; phytotoxicity